Analisis Manajemen Risiko pada Usaha Kuliner Mikro Kecil - Nissa, Selvira Agniatun; Burhanudin, Jajang (Jurnal Serambi Ekonomi dan Bisnis, 2024)
Micro small businesses in the culinary sector are one of the people's choices to improve their economic level. However, every business definitely has business risks. This research is intended to identify product risks, financial risks, human resource risks, marketing risks of small micro businesses in the culinary sector. The method used is a qualitative descriptive approach with interviews as the main data collection tool and also observation. The research results show that the main risks faced by this business are fluctuations in raw material prices, limited product durability, and high competition in the market. Apart from that, promotional limitations and operations that are not yet optimal are also challenges that disrupt business desires. Strengths include product innovation and affordable prices, weaknesses in terms of promotion and management operations, opportunities from innovative snack trends, and threats from the large number of competitors with similar products. This research emphasizes the importance of implementing risk management, including improving financial recording systems, improving marketing strategies, and improving operational quality, to support business extinction and competitiveness amidst competitive market dynamics.